'This is the end of the road for science': The mad doctor in Cold War horror comics. Issue 1 (1st April 2023) - Goodrum, Michael; Smith, Philip
This article concerns the representation of scientists, doctors and other agents of reason in Cold War horror comics. Such figures, we demonstrate, are typically represented as misguided, blind to the dangers of their creations or knowingly malevolent. The manifestation of this trend in the 1950s can be understood as a facet of the larger programme of post-Second World War social criticism found in the genre. When horror comics returned after the revision of the Code in 1971, some aligned with the anti-psychiatry movement. These comics portray scenarios in which the discovery of things man was not meant to know extends beyond weapons of war to the human psyche and where psychology as a discipline serves as a repressive apparatus interested primarily in the preservation of social norms rather than the emotional health of patients.